2020
DOI: 10.1039/c9nr06815e
|View full text |Cite
|
Sign up to set email alerts
|

Skin irritation potential of graphene-based materials using a non-animal test

Abstract: Graphene related materials, if prepared with non-irritant exfoliation agents, do not induce skin irritation on a 3D model of human epidermis, following the OECD guideline 439.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 35 publications
5
44
0
Order By: Relevance
“…In vitro and in vivo tests showed that the choice of the specific graphene-based material incorporated in the composites and the method of use are of key importance regarding the risks associated with the application of such materials for biomedical applications [51,52]. Our in silico toxicity screening studies of these nanomaterials (Table S2) [53] confirmed some potential for graphene, GO and rGO to induce skin sensitization due to the presence of conjugated dienes in their structures, supported by observations in both in vitro and in vivo models [54][55][56][57][58]. Moreover, hydroxynaphthalene derivatives such as rGO were demonstrated as estrogen receptor modulators [59].…”
Section: Resultssupporting
confidence: 65%
“…In vitro and in vivo tests showed that the choice of the specific graphene-based material incorporated in the composites and the method of use are of key importance regarding the risks associated with the application of such materials for biomedical applications [51,52]. Our in silico toxicity screening studies of these nanomaterials (Table S2) [53] confirmed some potential for graphene, GO and rGO to induce skin sensitization due to the presence of conjugated dienes in their structures, supported by observations in both in vitro and in vivo models [54][55][56][57][58]. Moreover, hydroxynaphthalene derivatives such as rGO were demonstrated as estrogen receptor modulators [59].…”
Section: Resultssupporting
confidence: 65%
“…GO (batch #GOB067) was supplied by Graphenea (San Sebastian, Spain). The complete characterization of the material was previously reported: 24 briefly, the elemental analysis showed average values of 59.40 ± 0.10% C, 1.40 ± 0.10% H, 0.07 ± 0.02% N and <36.6% O. The average lateral dimension, evaluated by laser diffraction in the GO slurry, was 15 100 ± 400 nm with a lateral size distribution located between 6000 and 30 000 nm.…”
Section: Chemicalsmentioning
confidence: 73%
“…For the complete GO physicochemical characterization, refer to our previous study performed with the same batch of GO. 24 The synthesis of GO was done in acidic media (H 2 SO 4 ) and the final dispersion of the material was in water. The purification was carried out by repeated washings in distilled water, but elemental analysis revealed that a small percentage of S (around 2%) remained in the final material, mostly as SO 4 2− .…”
Section: Chemicalsmentioning
confidence: 99%
“…Graphene Oxide flakes dimensions were checked by using dynamic laser light scattering (DLS) (90Plus/BI-MAS ZetaPlus multi angle particle size analyzer; Brookhaven Instruments Corp.) 12 . For all of the experiments, GO was used at a concentration of 50 mg/l, concentration that has been recognized as non-toxic for eukaryotic cells and, very recently, absolutely not toxic for cutaneous administration 31 36 .…”
Section: Methodsmentioning
confidence: 99%